Peran Dan Pelaksanaan Lembaga Arbitrase Dalam Menyelesaikan Konflik Hubungan Ketenagakerjaan Di Indonesia - Rohman Hakim (LP3M KH Yazid Karimullah Institute, 2021)
Disputes between workers and employers where no agreement can be reached can result in the end of the employment relationship or resignation. In general, this kind of situation will exacerbate conditions that are not expected by both parties, both workers and employers. The issues that are the focus of disputes, as explained in Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement (PPHI), include rights, interests, termination of employment, and conflicts between unions in one company. This study seeks to consider the arbitration option as an amicable method that suits the needs of the parties involved in resolving disputes between workers and employers, through normative and comparative juridical approaches, as well as secondary data analysis. The conclusion of this study is that arbitration has three key characteristics, namely a simple, fast, and relatively economical process, which can support the continuity of working relations in Indonesia. However, arbitration also has several drawbacks related to costs and fees for arbitrators or a team of arbitrators, which must be borne by both parties. Because of this, the possibilities for using arbitration as a dispute resolution mechanism in the future are likely to be limited.